Minority community participation in tourism development: A case of Malacca / Nur Shahirah Mior Shariffuddin and Muaz Azinuddin - Mior Shariffuddin, Nur Shahirah; Azinuddin, Muaz (UiTM Press, 2016)
The continuous development of tourism sectors world widely not only for the purpose to sustain the traditional resources but expanding the contemporary tourism products and cultural values. The combination of these two elements directly boosts up the economy of the country, situational contexts, and the local communities. Tourism development besides others is closely associated with communal efforts of all parties. Recognition of the tourism destinations could not be achieved by solidly depends on the government initiatives alone without the participation of the private sectors, industry players, NGO’s and the local communities. The involvement or participation of the community in tourism development is crucial in ensuring the development is meeting the economy and social objectives. This research note discusses the community capacity building toward state tourism development.